LINI HULU PRODUKSI SAWIT INDONESIA: PERSPEKTIF RANTAI PASOK - Fitriani Fitriani; Ambya Ambya; R Hanung Ismono; Dyah Aring Hepiana Lestari; Fembriarty Erry Prasmatiwi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
Smallholder oil palm plantations are still facing the challenge of solidity in increasing their collective action to influence the supply chain of the national and global palm oil industry. This study aims to analyze the upstream system of smallholder palm oil production in building the sustainability of the supply chain of the national palm oil industry from a supply chain perspective. The data collection method combines an empirical study approach and literacy. An empirical study was carried out to search for institutional portraits of farmers. Furthermore, the search for commodity flows and palm oil agro-industry actors was carried out using a supply chain scheme framework. Based on the discussion, it is concluded that the disclosure of the flow of information related to the volume, price, and supply value differs according to the stakeholders involved. The supply chain of upstream palm oil production starts from the production line of oil palm plantations to the fabrication of CPO/PKO and the fabrication of their derivatives. Oil palm farmers are the weakest parties in accessing prices, volumes, and purchasing capacity information. Independent and plasma oil palm plantation smallholders are the most vulnerable to problems of uncertainty, transparency, transaction costs, and institutions, as well as the determination of an undisclosed price share between the cooperative as an intermediary and the core company. The downstream supply chain of palm oil agroindustry (olein, biodiesel, and chemical industry) is dominated by stakeholders affiliating with national private plantation companies within the framework of vertical supply synergies. CPO/ PKO palm derivative processed agroindustry, which has no vertical affiliation with national plantation companies on the upstream side, was the weakest actor in dealing with uncertainty in the supply of raw materials.